The Relationship of Work Ethic and Professionalism to Service Employee Performance - Tri Deby Damayanti; Waizul Qarni; Atika (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2026)
Work ethic and professionalism are two critical factors often considered to influence employee performance in public service institutions, including the police sector. However, empirical evidence regarding their effects remains limited, particularly within the context of police service units. This study was conducted to assess the relationship between work ethic and professionalism on the performance of service employees at the Medan City Police Headquarters. A quantitative approach with an associative method was employed, involving a sample of 50 respondents selected through purposive sampling. Data were collected using questionnaires developed based on research variable indicators and analyzed using multiple linear regression, Pearson correlation, classical assumption tests, and hypothesis testing. The results showed that work ethic did not have a significant effect on employee performance, whereas professionalism had a positive and significant effect. Furthermore, work ethic and professionalism simultaneously demonstrated a significant influence on service employee performance. These findings confirm that enhancing professionalism—including technical competence, analytical skills, and communication skills—is a key strategy to improve service performance. This study provides an empirical foundation for public sector human resource management development, particularly within the context of police institutions.